Annie Pederson : Break of Day - Book 3 - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2023)
"Annie Pederson's happily ever after is finally within sight . . . if she can stay alive long enough to grasp it. Return to the beloved town of Rock Harbor in the final installment of the Annie Pederson trilogy by bestselling suspense author Colleen Coble"--
Keywords: Single mothers -- Fiction; Christian fiction; Thrillers (Fiction); Romance fiction; Novels